Impact of Water Deficits on Senescence and Carbon Redistribution in Drought-Tolerant and Drought Susceptible Wheat Varieties - Saeedipour, Saeed (Global Journal of Food and Agribusiness Management, 2024)
Remobilization and transfer of the stored food in vegetative tissues to the grains in monocarpic plants require the initiation of whole plant senescence. However, mechanisms by which plant senescence promotes remobilization of assimilates are rather obscure. This study examined the relationship between the senescence induced by water deficits and C remobilization during grain filling. Two wheat cultivars (TRITICUM AESTIVUM L.), Marvdasht and Zagros (sensitive and tolerant to terminal season drought, respectively) grown at a day:night temperature of 22:15°C from anthesis were held as well watered controls (field capacity), or subject to water deficit (50% FC) imposed either from anthesis to 14 days later (WS1) or from 14 days after anthesis to maturity (WS2). Relative water content, photosynthetic activity, chlorophyll content, soluble proteins of flag leaves, level of hexose sugars, sucrose and fructans in the peduncle (enclosed by the flag leaf sheath) and the penultimate internode and grain yield assessed. Results showed that water deficits enhanced the senescence by accelerating loss of leaf chlorophyll and soluble proteins and the loss was more under WS2 than WS1. The net CO2 assimilation rate (PN) in flag leaves during water deficit display a strict correlation with the drought sensitivity of the genotypes and showed an early reduction in Marvdasht. Water stress, both at WS1 and WS2, facilitated the reduction in concentration of total soluble sugars and fructans in the internodes but increased the sucrose level there, promoted the re-allocation of pre-stored C from the peduncle and penultimate to grains. There was an increase in internodes fructose and a fall in fructan level that preceded the loss of dry matter associated with water stress. WS2 resulted in more deleterious effect on grain yield than WS1 in both cultivars and led to a smaller kernels and lesser aerial biomass at maturity. The loss was more in Marvdasht than Zagros. Our results suggest that the senescence and remobilization promoted by water deficits during grain filling are coupled processes in wheat and mass of soluble sugars in the stems is premier than sugar remobilization efficiency. Varietal differences in the extent of such trait existed. It would be advantageous to select genotypes with greater capacity to do this under water deficit conditions.